Eminence, Finney County - Doll, Allison (Kansas State University, The Chapman Center for Rural Studies, 2016)
This brief history of Eminence, Kansas chronicles the story of a rural town that went from its founding, to becoming county seat, and then ceasing to exist in under a decade. Located in now defunct Garfield County, Eminence was flourishing on the plain when a fight for the new county’s seat destroyed not only both towns, but also the county itself. This study uses plat maps, newspaper articles, historic photographs, site studies, and an interview with a former owner of the town site.
Allison Doll, “Eminence, Finney County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/181.
Keywords: C.J. Buffalo Jones; Finney County; Garden City; Garfield County; Lyman Naugel; Eminence